Pengaruh Model Pembelajaran Teams Games Tournament (TGT) Terhadap Kemampuan Kerjasama pada Pembelajaran PPKn Siswa Sekolah Dasar - Nurluthfiana, Fadia; Rondli, Wawan Shokib (Peneliti.net, 2025)
The low level of student collaboration ability in Civics learning is the background for this research. Using the Teams Games Tournaments (TGT) cooperative learning model is an alternative to overcome this. Quasi-experimental method One group pre-test and post-test design was used in this research. Tests and observations are the data collection techniques used. The results obtained before learning had a class average of 57.9. Meanwhile, after implementing the experimental class treatment, the average obtained was 75.95. The research obtained results from the Teams Games Tournament model which influenced fourth grade students at SDN 1 Mijen in PPKn learning, their collaborative abilities increased. Seen in the Sig value. Sample Paired t-test 0.001 < 0.05. Providing treatment using the Teams Games Tournament Model in one treatment can increase scores with a pretest average of 57.9 to a posttest average of 75.95